Examining the contributions of radial and lamellar optic flow gain to quiet stance - Lisa K. Lavalle; Atara Lipson; Sara E. Weinberg; Taylor W. Cleworth (Scientific Reports)
Abstract The visual system plays an integral role in maintaining quiet stance. When visual feedback is amplified by increasing the gain of optic flow, individuals develop a tighter control of upright stance. The pattern of optic flow can also vary depending on the eccentricity of gaze, where looking to the side or down can increase the proportion of lamellar, compared to radial optic flow. Further, previous work has shown differences between visual motion perception when exposed to varying types of optic flow. It currently remains unknown how the type of optic flow contributes to postural control while under the influence of modified gain. Therefore, this study aimed to better understand how the gain of radial and lamellar optic flow, manipulated by changing head orientation, contributes to balance control during quiet stance among healthy adults. Participants were recruited to stand quietly with feet together on a foam pad placed over a force plate while wearing a virtual reality head-mounted display Three head orientations (forward, 45° left, 45° down) were used to expose participants to primarily radial (forward) or lamellar (side or down) optic flow. For each head orientation, participants completed 3 trials, where the gain of optic flow was amplified to either 1x, 4x, or 16x normal optic flow. Overall, an increase in optic flow gain decreased amplitude and increased frequencies of balance measures. Some mediolateral amplitude measures of balance were also greatest when looking to the side; however, the effect of optic flow gain on center of pressure and head displacement were similar across head orientations.